Coastal Tourism: Development Strategy of Loang Baloq Beach in Lombok Island, Indonesia - NUGROHO, M. Setyo; MAS’UD, Riduan; KHALIK, Wahyu; FAHDIANSYAH, Restu; AZIZOMA, Rusman; ROMDHINI, Mamika Ujianita; AMINY, Muhammad Muhajir (Journal of Environmental Management and Tourism; Vol 13 No 4 (2022): JEMT, Volume XIII, Issue 4(60), Summer 2022DO - 10.14505/jemt.v13.4(60).04, 2022)
This research aims to generate a development strategy formulation of tourist attraction Loang Baloq beach in Mataram city. This research is a qualitative study with a survey method and description. Data is collected using observation technique, interview (purposive sampling), questionnaire distribution (acci-dental sampling), and documentation study in the book, articles, and other sources. The data analysis technique uses qualitative description, Likert scale, and SWOT analysis to formulate the appropriate strat-egy for Loang Baloq beach development. This research shows that Loang Baloq beach is in the first quadrant, indicating progressive strategy (grand strategy). It means that Loang Baloq beach is in prime condition. Therefore, it enables maximum achievement for growth and progress. The suggested strategy is the strategy that seizes the opportunity and highlights the strengths. Then, the alternative strategy which is generated is based on S-O strategy, S-T strategy, W-O strategy, and W-T Strategy.